PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN SIMULASI PHET TERHADAP MINAT DAN HASIL BELAJAR FISIKA SISWA SMA MUHAMMADIYAH 9 MAKASSAR PADA MATERI GERAK - Bahrur Rahman Hasba; Muh Farel; Nur Ali; Nur Azisa; Wahida; Nadiyahturrahmah; Delha Trijunianti; Fauzan Mutawakkil; Syahrul Ramadani; Nur Faidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low students' interest and learning outcomes in physics, particularly on the topic of Motion, remain a challenge in the teaching and learning process. One alternative instructional approach to address this issue is the implementation of the Discovery Learning  model assisted by PhET Interactive Simulations. This study aimed to examine the effect of the Discovery Learning  model assisted by PhET Interactive Simulations on the learning interest and physics learning outcomes of eleventh-grade students at SMA Muhammadiyah 9 Makassar. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 32 students in Class XI A as the experimental group and 32 students in Class XI B as the control group. Data were collected through learning achievement tests and a learning interest questionnaire and analyzed using descriptive statistics, normality tests, homogeneity tests, N-Gain analysis, and the Independent Samples t-test. The results revealed that the experimental group's mean score increased from 44.50 to 83.20, while the control group's mean score increased from 43.95 to 71.35. Students' average learning interest also improved from 30.87 to 84.50. Furthermore, the Independent Samples t-test yielded a significance value of 0.001 (p < 0.05), indicating that the Discovery Learning  model assisted by PhET Interactive Simulations had a significant positive effect on students' learning interest and physics learning outcomes in the topic of Motion.